2019
DOI: 10.3390/biom9090472
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblasts and Their Pathological Functions in the Fibrosis of Aortic Valve Sclerosis and Atherosclerosis

Abstract: Cardiovascular diseases, such as atherosclerosis and aortic valve sclerosis (AVS) are driven by inflammation induced by a variety of stimuli, including low-density lipoproteins (LDL), reactive oxygen species (ROS), infections, mechanical stress, and chemical insults. Fibrosis is the process of compensating for tissue injury caused by chronic inflammation. Fibrosis is initially beneficial and maintains extracellular homeostasis. However, in the case of AVS and atherosclerosis, persistently active resident fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 101 publications
(107 reference statements)
0
44
0
4
Order By: Relevance
“…Oxidative stress is defined as excessive reactive oxygen species (ROS) relative to antioxidant defenses, and is advanced in HF ( 50 ). ROS can mediate cell apoptosis and MMPs, leading to ECM remodeling ( 51 ). MMP3 and MMP9 are extracellular zinc proteases that serve vital roles in the development and progression of atherosclerosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is defined as excessive reactive oxygen species (ROS) relative to antioxidant defenses, and is advanced in HF ( 50 ). ROS can mediate cell apoptosis and MMPs, leading to ECM remodeling ( 51 ). MMP3 and MMP9 are extracellular zinc proteases that serve vital roles in the development and progression of atherosclerosis ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines cause both paracrine and endocrine effects that mediate local and systemic responses [28,29]). According to a recent review [30], the expression of pro-inflammatory cytokines, such as TGF-β, TNFα, IL-1β, and IL-6, is consistently identified in aortic-valve sclerosis. These cytokines seem to be produced by leaflets' activated fibroblasts, whose differentiation, proliferation, and matrix remodeling participate in the endothelial damage of aortic valve leading to the valve thickening [30].…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent review [30], the expression of pro-inflammatory cytokines, such as TGF-β, TNFα, IL-1β, and IL-6, is consistently identified in aortic-valve sclerosis. These cytokines seem to be produced by leaflets' activated fibroblasts, whose differentiation, proliferation, and matrix remodeling participate in the endothelial damage of aortic valve leading to the valve thickening [30]. IL-6 is also known to be involved in the endothelial dysfunction of other cardiovascular diseases by interfering with endothelial nitric oxide synthase expression [31] and, in conjunction with C-reactive protein, is regarded as an indicator of chronic or systemic low-grade inflammation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [ 16 ] distinguished five phenotypes in the VICs family: embryonic progenitor endothelial/mesenchymal cells, quiescent VICs (qVICs), activated VICs (aVICs), progenitor VICs (pVICs), and osteoblastic VICs (obVICs). The cytological features of activated VICs (aVICs) correspond to those of myofibroblasts, described in valves by numerous authors and reported to play an important role in valve fibrosis contributing to degenerative processes such as valve sclerosis and atherosclerosis [ 23 ]. However, Combs et al claimed that neither the commitment of VICs to the separate, fixed lineages nor the specific origin of VIC in distinct valve compartments have been unequivocally defined and proved [ 24 ].…”
Section: Introductionmentioning
confidence: 99%